FACTUAL AND STATISTICAL ANALYSIS OF GLOBAL RULE OF LAW TO ESTABLISH WHETHER JUSTICE IS A MYTH OR REALITY IN PAKISTAN - Sundus Rauf; Hadia Ashraf; Sobia Sifarish (International Journal of Contemporary Issues in Social Sciences, 2024)
Justice is considered to be the hallmark of a functioning state. It is the only pillar which is responsible to provide a strong foundation to the state supporting other organs. The enforcement of fundamental rights enshrined in the Constitution of 1973 is not possible without rule of law and access to justice through strong judicial system. This paper is intended to analyze the fact and statistics which are available on the international data sites, to establish the current situation of rule of law in our country. The information about Pakistan has also been compared with that of other selected countries to observe the recent status of Pakistan among them. The required information has been collected using qualitative research methodology which was then compared and explained through descriptive approach. The research also helped in exploring the impacts of this rule of law situation and limited administration of justice, referring to the major causes responsible for it, ending the study with a solid conclusion that justice is a myth in our country and needed to be brought to reality by taking revolutionary and reformative measures.